Salivary molecules of bone remodeling and tissue repair after head and neck radiotherapy - Eduardo Morato de OLIVEIRA; Rafael Soares GUIEIRO; Bárbara Lima CRUZ; Maria Cássia Ferreira de AGUIAR; Janine Mayra da SILVA; Tarcília Aparecida SILVA; Patrícia Carlos CALDEIRA (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract Head and neck radiotherapy causes quantitative and qualitative changes in saliva. The objective of this case-control study was to evaluate the salivary biomarkers associated with bone remodeling and tissue repair in patients submitted to radiotherapy for head and neck cancer treatment, compared with non-irradiated individuals. Total unstimulated saliva was collected for ELISA assay analysis of receptor activator for nuclear factor κ B (RANK) and its ligand (RANK-L), osteoprotegerin, matrix metalloproteinase-9/ tissue inhibitor of metalloproteinase-2, vascular endothelial growth factor, and epidermal growth factor. Statistics were performed, and revealed that salivary RANK (p = 0.0304), RANK-L (p = 0.0005), matrix metalloproteinase-9/ tissue inhibitor of metalloproteinase-2 (p = 0.0067), vascular endothelial growth factor (p = 0.0060), and epidermal growth factor (p < 0.0001) were reduced in patients, compared with the control group. Osteoprotegerin did not differ between the groups (p = 0.3765). Salivary biomarkers did not differ according to radiotherapy completion time (p > 0.05). In conclusion, the lower output of the salivary molecules - essential for bone remodeling and tissue repair - may disrupt tissue homeostasis and play a role in the pathogenesis of the radiotherapy-induced deleterious effects in the oral cavity.